2002
DOI: 10.1091/mbc.01-07-0380
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin-dependent Transferrin Receptor Recycling by Endosome-derived Clathrin-coated Vesicles

Abstract: Previously we described clathrin-coated buds on tubular early endosomes that are distinct from those at the plasma membrane and the trans-Golgi network. Here we show that these clathrincoated buds, like plasma membrane clathrin-coated pits, contain endogenous dynamin-2. To study the itinerary that is served by endosome-derived clathrin-coated vesicles, we used cells that overexpressed a temperature-sensitive mutant of dynamin-1 (dynamin-1 G273D ) or, as a control, dynamin-1 wild type. In dynamin-1 G273D -expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
158
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 57 publications
(92 reference statements)
17
158
1
Order By: Relevance
“…5C). In addition, other compounds that have been shown to inhibit recycling of the TfR receptor (28,29) and of the AT 1A angiotensin II receptor (13), the phosphoinositide 3-kinase inhibitors wortmannin and LY294002, and brefeldin A also inhibit CB1R externalization induced by AM281 (data not shown). These compounds have a broad range of cellular effects; they unravel the constitutive endocytosis of CB1R and indicate that AM281 may act through constitutive recycling but do not allow unambiguous identification of the intracellular pathways involved.…”
Section: Cb1r Is Constitutively Endocytosed and Am281-induced Externamentioning
confidence: 91%
“…5C). In addition, other compounds that have been shown to inhibit recycling of the TfR receptor (28,29) and of the AT 1A angiotensin II receptor (13), the phosphoinositide 3-kinase inhibitors wortmannin and LY294002, and brefeldin A also inhibit CB1R externalization induced by AM281 (data not shown). These compounds have a broad range of cellular effects; they unravel the constitutive endocytosis of CB1R and indicate that AM281 may act through constitutive recycling but do not allow unambiguous identification of the intracellular pathways involved.…”
Section: Cb1r Is Constitutively Endocytosed and Am281-induced Externamentioning
confidence: 91%
“…Recycling of Transferrin Is Independent of Clathrin TD Function-Clathrin coats in addition to the plasma membrane and the TGN have also been observed on endosomes (23,24,47), where they are involved in polarized sorting to the basolateral surface in epithelial cells, among possible other functions (48). A highly dynamic form of endosomal clathrin (termed G-clathrin) has been postulated to regulate rapid recycling (27).…”
Section: Reduced Mobility Of Ap-1-and Gga-coated Carriers Uponmentioning
confidence: 99%
“…Nocodazole depolymerizes microtubules and promotes dispersal and tubulation of the Golgi apparatus (Turner and Tartakoff, 1989). Brefeldin A disrupts the Golgi apparatus (Lippincott-Schwartz et al, 1990) but also has been reported to interfere with normal sorting and recycling of the holotransferrin bound to its receptor in endocytic vesicles (Xia and Shen, 2001;van Dam and Stoorvogel, 2002). Tyrphostin A8 (AG10) inhibits a GTPase (Rab17) necessary for the fusion of vesicles and endosomes in the apical region of polarized epithelial cells (Lütcke et al, 1993;Hunziker and Peters, 1998;Zacchi et al, 1998;Knight et al, 1995;Hughson and Hopkins, 1990).…”
Section: Effects On Iron Absorption Of Inhibiting Vesicular Transportmentioning
confidence: 99%